Mother-child exposure to polychlorinated biphenyls and organochlorine pesticides in the Northern Finland cohort (NUGEN) - Palaniswamy, Saranya; Salah, Soha; Přibylová, Petra; Kukučka, Petr; Laatio, Liisa; Sieppi, Elina; Kummu, Maria; Rautio, Arja; Myllynen, Päivi; Abass, Khaled (Environmental toxicology and pharmacology, 2025)
Limited knowledge exists on persistent organic pollutants (POPs), including polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs), in mother-child pairs from Northern Finland. This study examines plasma PCB and OCP concentrations and their determinants. Blood plasma concentrations of 13 PCBs and 6 OCPs were measured in mothers and in cord samples from the NUGEN birth cohort (N = 102, 2012-2014). Correlations between maternal and cord POPs were assessed using Spearman correlation, and linear regression identified factors influencing lipid-adjusted POPs. Maternal age and alcohol consumption during pregnancy were positively associated with PCBs and OCPs. Pre-pregnancy BMI and weight change during pregnancy were inversely associated with PCBs, but positively with p,p'-DDE in children. Increasing parity and smoking were associated with lower PCBs. Maternal fish consumption was associated with higher PCBs in children. Finnish pregnant women had lower PCBs and OCPs than other European populations. These findings inform exposure risk assessment and prevention strategies.
Keywords: těhotenství; pesticidy; zpožděný efekt prenatální expozice; fetální krev; lidé; Adult; Pesticides; Female; dítě; Finland; Hydrocarbons, Chlorinated; Humans; Infant, Newborn; Environmental Pollutants; matka - expozice noxám; kohortové studie; Cohort Studies; mužské pohlaví; mladý dospělý; novorozenec; Prenatal Exposure Delayed Effects; Pregnancy; ženské pohlaví; Young Adult; Finsko; chlorované uhlovodíky; Male; látky znečišťující životní prostředí; Child; dospělí; polychlorované bifenyly; Fetal Blood; Maternal Exposure; Polychlorinated Biphenyls